Discover the Fascinating Insights: Public School Students in Jordan Embrace Distance Education - Smadi, Mona; Hijazi, Dima; Maharmah, Hamza; Al Masri, Amaal (Journal of Ecohumanism, 2024)
This study aimed to address the question, "How effective is the use of distance education?" by exploring it from the perspective of public-school pupils. This descriptive survey study aimed to quantify the impact of gender differences in viewpoints throughout the first half of 2023. The study’s 300 participants were chosen randomly from male and female pupils enrolled in public schools under the Wadi el-seer Directorate of Education. In all, 150 males and 150 females made up the sample. Findings were encouraging; an impressive mean score of 4.78 was attained by the top-rated statement, "Through the use of distance learning, my academic experience has been greatly enhanced," highlighting the favorable influence of remote learning on academic experiences. The statements "Participating in classes remotely has increased my interest and motivation" (4.67) and "Distance education facilitates discussions and dialogues about educational problems" (4.59) illustrate its capacity to enhance motivation and encourage meaningful discussions. While statements like "Education grew in popularity and piqued my curiosity" (3.60) and "I believe that distant education sufficiently equips me to face professional problems" (3.60) indicate areas that need improvement, the overall domain score of 4.30 confirms a generally positive perception of distance education.